Energy Politics and Warfare: How International Energy Interests Shape Alliances in the Russian-Ukrainian Conflict - Madubuko, Christian C. (American Journal of International Relations, 2024)
Purpose: This study aims to critically examine the intricate interplay of energy politics and military strategy within the context of the ongoing Russian-Ukrainian conflict. It posits that energy resources - specifically oil and natural gas - serve as pivotal factors that shape strategic alliances, influence geopolitical manoeuvring, and dictate the foreign policy trajectories of international actors, including the United States, the European Union, and China. Materials and Methods: The research employs a qualitative methodology that is underpinned by a series of semi-structured interviews conducted with a diverse cohort of policymakers, energy analysts, and industry stakeholders. Through this empirical approach, the study explores the participants' perceptions regarding the nexus between energy dynamics and security policymaking. In addition to the qualitative interviews, the investigation analyses a range of qualitative materials, including public statements, policy documents, and corporate strategic outlines. Discourse analysis is utilized to further uncover the mechanisms through which energy companies exert influence on governmental policies and military postures. Findings: The anticipated findings are expected to provide a nuanced understanding of the centrality of energy resources in influencing military strategies and fostering international coalitions. This analysis will contribute to an enriched scholarly discourse that informs not only theoretical frameworks in international relations but also practical applications in global energy governance and security. Implications to Theory, Policy and Practice: The inquiry underscores the imperative for a multifaceted and informed policy approach that acknowledges the profound implications of energy resources on national interests and global stability. By integrating energy considerations into security policymaking, the study advocates for a reassessment of traditional strategic paradigms that often overlook the complexities arising from energy interdependence.